Solar Fuels Harvesting from Carbon Dioxide Conversions - Lei, Yu; Nuraje, Nurxat; Yashkarova, Marziya; Kudaibergenov, Sarkyt (Nanoscience & Nanotechnology-Asia, 2012)
The review provides a comprehensive overview to the research progress of photocatalytic conversion of carbon dioxide reduction. Excessive anthropogenic activities increased carbon dioxide level in the atmosphere, which led the global warming. Meanwhile, the capability of producing carbonaceous fuels was linked to the issue of energy security. Therefore, the photocatalytic conversion by reducing carbon dioxide become crucial to solve both previous mentioned problems. Materials from inorganic semiconducting particles to organic molecule are explored in this field of research. The research progress updates in this review cover the techniques of changing morphology, coating with various cocatalysts, coupling with cavity space material, and synthesizing complex of organic molecule and inorganic photocatalysts. The theories of photocatalytic conversion related to kinetics and thermodynamics, and the measurement criteria of experimental performances are described.
Keywords: energy material